The Neapolitan School: Francesco Durante (1684-1755) - Aspects of Manuscript Dissemination, Misattributions, and Reception - Dietz, Hanns-Bertold (Música em Perspectiva, 2009)
After the Austrian conquest of Naples in 1707, Masses, motets and Psalm settings, by Francesco Mancini, Nicola Fago, Domenico Sarro and the still little-known Francesco Durante, made their way into Bohemia, the Austrian Netherlands, and Saxony. All of Durante's early exported pieces of church music are found in these locations only. From the Zenith of his career, 1738 to 1755, dated manuscripts cover almost every year. The period includes all of the works upon which rests Durante's posthumous fame. During the nineteenth century, his church music, especiallly his works in "Palestrina style," became objects for collectors of "ancient music." The demand for sacred works by Durante and other Neapolitan composers led to misattributions of manuscripts, not always out of ignorance. During the second-half of the nineteenth century, changing attitudes toward church music, the Bach restoration, and the emergence of a view of history tinged with nationalistic overtones led to a change in Durantes's historic position. By 1904, The "Epoch of the Neapolitan School: Leo and Durante, 1725-1766" had been replaced by "The Age of Bach and Handel." The lack of interest in Neapolitan church music that followed led to a neglect of scholarly studies until the second half of the twentieth century, when musicologists began to revive the topic.